Therapeutic Exergaming and Its Feasibility in Developing Countries Setting: Review Article - Mubarak, Husnul; Andi Amirah Shaleha Junaed (Faculty of Medicine, Hasanuddin University., 2024)
Introduction: Games have an important role from a social point of view in human and cultural development. Exergaming is a form of digital gaming that combines video games and physical activity that uses a motion tracking device to record gestures and complete gameplay on a screen. Therapeutic exergaming has the potential to facilitate improved balance, including reducing center of pressure (CoP) variability, home-based exercise for older adults, and exercise for people with balance disorders. Method: for this literature review we searched journals taken from search engines such as google, google scholar, Pubmed, and PubMed Central, published from the inception of the respective databases to June 2022. The keywords therapeutic exergaming, exergaming, video game, physical therapy, consoled game, virtual reality were used in writing this literature. The literature search and journal reading were limited to sources which was free and written in English. We addressed several aspects of exergaming such as the device sensor feedback, its application to augment therapy and to manage diseases, and its implementation in developing countries. Conclusions: The benefits of exergaming have been widely studied and are known to have many positive effects on health, such as improving cognitive function, increasing physical activity, exercising balance, and improving vascular function. Exergaming has become an alternative therapy in Huntington's disease, Parkinson's disease, and as a means of gait rehabilitation in geriatric patients. Exergaming also has the potential to reduce the risk of obesity in children.